2021
DOI: 10.3389/fped.2021.638449
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of the Bayley-III Cognitive Scores at 6 Months for Cognitive Outcomes at 24 Months in Very-Low-Birth-Weight Infants

Abstract: Purpose: To assess the predictive validity of the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III) cognitive scores at 6 months of corrected age (CA) for cognitive outcomes at 24 months of CA in very-low-birth-weight (VLBW) infants and investigate the predictors of change in cognitive outcomes.Methods: We retrospectively evaluated VLBW children enrolled in the Taiwan Premature Infant Follow-up Network between 2010 and 2015 and completed the Bayley-III at CA of 6 and 24 months. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In fact, to the best of our knowledge, there are a growing number of studies evaluating neurodevelopment in infants around 6 months of age [37][38][39]. A study had shown that infants with neurodevelopmental delays would have better neurodevelopmental outcomes in future if interventions were given at 6 months of age [40]. This might highlight the importance of early identification and intervention of high-risk infants to promote an improved neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, to the best of our knowledge, there are a growing number of studies evaluating neurodevelopment in infants around 6 months of age [37][38][39]. A study had shown that infants with neurodevelopmental delays would have better neurodevelopmental outcomes in future if interventions were given at 6 months of age [40]. This might highlight the importance of early identification and intervention of high-risk infants to promote an improved neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This developmental assessment tool is usually administered by psychologists, paediatricians or physiotherapists and takes 30–70 min to complete, with extra time needed for scoring 26 . It is resource intensive and is generally used for high risk populations, such as preterm or low birth weight infants 27 . Studies of its use in the general population are limited, but evidence suggests that if it was performed in early life, particularly the first 24 months, it would have poor to modest correlations with later cognitive ability 28 …”
Section: Discussionmentioning
confidence: 99%
“…26 It is resource intensive and is generally used for high risk populations, such as preterm or low birth weight infants. 27 Studies of its use in the general population are limited, but evidence suggests that if it was performed in early life, particularly the first 24 months, it would have poor to modest correlations with later cognitive ability. 28 Our study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the numbers and grades of risk factors (Table 1), a corrected age (CA) to visit for neurodevelopmental surveillance and follow-up periods are suggested in Fig. 1 [3,5,10,13,14].…”
Section: Early Neurodevelopmental Assessment Planmentioning
confidence: 99%
“…For example, if any special diagnosis is made, such as genetic or neurodegenerative diseases, the follow-up schedule should be individualized through experts' and multidisciplinary care plans. Although the Bayley Scales of Infant Development (BSID) is an extensive formal developmental assessment tool for diagnosing developmental delays in early childhood for 1 to 42 months old babies (Table 2), it cannot predict long-term outcomes of development, especially when assessed at a young age such as before CA of 24 months old [13,15]. For those still undiagnosed with extremely preterm birth (<28 weeks) or extremely low birth weight (<1,000 g), BSID is strongly recommended at a CA of 36 months.…”
Section: Early Neurodevelopmental Assessment Planmentioning
confidence: 99%